Identificando tipos de personalidade na dança de salão - Fabiano, Henrique Ricardo Gazzi [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Many studies have shown a variety of benefits that the practice of Ballroom Dancing can bring, such as leisure and entertainment, the release of tension from a stressful routine, improving relationships, expanding social contacts. The rationale of this study is by the need to evaluate a different sphere of life of people involving the structure that is the personality. The man is humanized in contact with other men and the culture it is almost impossible to grow it in isolation, that is, are the social relationships that allow men to become human and her personality structure. The relationship brought about by the ballroom dancing can benefit the development of personality or simply put individuals in situations that provide a greater understanding of yourself, as this activity has characteristics that greatly facilitate social contact between people who practice it as the relationship between gentleman and lady for a dance, the contact with people in different classes, social events where it is practiced and even the music that is danced. This work aimed to be able to identify the type or types, the most common personalities exist in one group of participants in a course of Ballroom, based on the technique of Enneagram developed and disseminated by Gurdjieff, whose characteristic is to divide into nine different personality types. Participants were 42 students of the extent to ballroom dancing. We administered a questionnaire to identify the personality of each participant and then there was a second observation time the behavior of six participants in the class for confirmation of your psychological type to issofoi used a checklist developed by the author. Was also investigated whether there are differences of gender and psychological types who seek more such activity. The conclusions are that there are a large number of persons type 9, more than 42% and are predominantly male, since... (Complete abstract click electronic access below)

Muitos estudos já mostraram uma variedade de benefícios que a prática da Dança de Salão pode trazer, tais como o lazer e a diversão, a liberação de tensões provenientes de uma rotina estressante, melhoria das relações afetivas e a expansão dos contatos sociais. A justificativa deste estudo se dá pela necessidade de avaliar uma outra esfera da vida das pessoas envolvendo sua estrutura que é a personalidade. O homem se humaniza no contato com outros homens e com a cultura, sendo quase impossível que ele se desenvolva no isolamento, ou seja, são os relacionamentos sociais que possibilitam ao homem tornar-se humano e estruturar sua personalidade. O relacionamento propiciado pela dança de salão pode beneficiar o desenvolvimento da personalidade ou simplesmente colocar cada indivíduo em situações que propiciem um maior conhecimento de si mesmo, já que esta atividade tem características que facilitam muito o contato social entre as pessoas que a praticam como a relação entre cavalheiro e dama durante uma dança, o contato com pessoas diferentes nas aulas, os eventos sociais onde ela é praticada e até mesmo a música que é dançada. Este trabalho teve como objetivo principal conseguir identificar o tipo, ou os tipos, mais comuns de personalidades existentes em um grupo de participantes de um curso de Danças de Salão, com base na técnica do Eneagrama desenvolvida e difundida por Gurdjieff, cuja característica é a de dividir a personalidade em nove diferentes tipos. Participaram do estudo 42 alunos do curso de extensão em danças de salão. Foi aplicado um questionário para identificar a personalidade de cada participante e posteriormente houve um segundo momento de observação do comportamento de seis participantes durante as aulas para a confirmação de seu tipo psicológico descrito pelo questionário, para isso foi utilizada uma lista de checagem elaborada... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Dança; Eneagrama; Mapeamento dos tipos psicológicos; Psicologia transpessoal; Ballroom dance; Personalities; Enneagram